Emerging Arboviral Diseases in Pakistan: Epidemiology and Public Health Implications - Muhammad Ammar; Muhammad Moaaz; Chaoxiong Yue; Yaohui Fang; Yanfang Zhang; Shu Shen; Fei Deng (Viruses)
Arboviruses pose significant public health challenges globally, particularly in Pakistan, where deforestation, climate change, urbanization, inadequate sanitation, and natural disasters have all contributed to the spread of mosquito-borne flavivirus diseases like dengue fever. The lack of a thorough national surveillance system has made it difficult to determine the extent and distribution of these diseases. Concern has been raised by recent outbreaks of West Nile virus (WNV) and chikungunya (CHIKV) epidemics, which may lead to Zika virus (ZIKV) outbreaks in the future. Additionally, hospital-based surveillance has detected the Japanese encephalitis virus (JEV) in the region. Evidence also points to the presence of additional arboviruses in healthy populations, such as the Karshi virus (KSV), Tamdy virus (TAMV), Crimean–Congo hemorrhagic fever virus (CCHFV), and severe fever with thrombocytopenia syndrome virus (SFTSV). This review aims to address the risk factors linked to these diseases, provide specific policy recommendations for efficient disease prevention and control, and describe the epidemiological trends of these diseases in Pakistan while emphasizing the critical need for improved surveillance and thorough epidemiological investigations.